Short selling, margin buying and stock return in China market1. (13th September 2016) - Li, Rui; Li, Nan; Li, Jiahui; Wu, Chongfeng
Abstract: It is well argued that short sellers are informed traders, and short interests predict future stock returns significantly. However, most researches neglect margin buyers, as twin sisters of short sellers, and keep silent about their impact on stock returns. In this article, we demonstrate that margin buyers significantly impact predictive power of conventional short measures. We document that conventional short measures neglecting margin‐buying activities, short interest ratio (SIR) and days to cover (DTC) fail to predict stock return unless our analysis is confined to lightly margin bought stocks. We also show that short‐margin trading ratio (SMTR), revised short measure with consideration of margin buying, predict stock return more sharply. What is more, we can form profitable portfolios by the new short measure.